Correction: Integrative analysis of genomic variants reveals new associations of candidate haploinsufficient genes with congenital heart disease. - Enrique Audain; Anna Wilsdon; Jeroen Breckpot; Jose M G Izarzugaza; Tomas W Fitzgerald; Anne-Karin Kahlert; Alejandro Sifrim; Florian Wünnemann; Yasset Perez-Riverol; Hashim Abdul-Khaliq; Mads Bak; Anne S Bassett; et al. (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1009679.].